Optimal support techniques when providing mechanical ventilation to patients with acute respiratory distress syndrome - Parissopoulos, Stelios; Mpouzika, Meropi; Timmins, Fiona (My University, 2017)
Background: Adult respiratory distress syndrome (ARDS) is a type of acute diffuse lung injury characterized by severe inflammation, increased pulmonary vascular permeability and a loss of aerated lung tissue. The effects of high fraction of inspired oxygen (FiO2) include oxygen toxicity manifested by damage to the lung parenchyma in the acute phase of lung injury. There is still a high mortality rate among this group of patients, so clinically sensitive evidence-based interventions are paramount to maximize survival chances during critical care. Aims and objectives: The aim of this article is to explore the current opinion concerning optimal mechanical ventilation support techniques for patients with acute respiratory distress syndrome. Search strategy, inclusion and exclusion criteria: A literature search of clinical trials and observation studies, reviews, discussion papers, meta-analyses and clinical guidelines written in English up to 2015, derived from the databases of Scopus, CINAHL, Cochrane Library databases and PubMed was conducted. Conclusions: Low tidal volume, pressure limitation and prone positioning in severe ARDS patients appear to be of some benefit. More research is required and further development and use of standardized protocols is an important strategy for reducing practice variations across disciplines, as well as giving clear guidelines to nurses practising in critical care. There is also evidence that this syndrome is under-diagnosed and the utilization of lung protective ventilation is still variable. Relevance to clinical practice: It is important that nurses have underlying knowledge of both aetiology of ARDS and ventilation management, and that they monitor patients very closely. The adoption of a low tidal ventilation protocol, which is based on quality evidence guidelines, the value of rescue therapies and patient observation practices in the overall patient management, and the need to place emphasis on long-term patient outcomes, all these emerge as key factors for consideration and future research. However, there is also a need for more research that would explore the unique contribution of nurses in the management of this patient group, as it is difficult to discern this in the current literature.
Keywords: ARDS; Adult intensive care; Lung protective ventilation; Mechanical ventilation; Pressure limitation; Tidal volume